2019
DOI: 10.4236/wjet.2019.73035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pneumatic Boxing Gloves on Impact Kinematics and Their Relationship to Impact Forces

Abstract: This study was aimed at improved understanding of the mechanisms of previously reported protective effects of a pneumatic boxing glove. A Motion Capture System was used to obtain velocity data from four different boxing gloves dropped on to a force plate from nine heights ranging from 1 to 5 metres. Two gloves were of the conventional type but differed in mass. The other two were prototype pneumatic gloves. One of these (SBLI) had a sealed bladder while the other (ARLI) incorporated a port allowing air exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…To reduce the risk of injury to both the striker and the striker's opponent, boxing gloves were implemented within the sport of boxing (1,3,(5)(6)(7)(8)12,13). Diesselhorst et al found that wearing hand protection when striking greatly reduces the risk of hand injury (3).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the risk of injury to both the striker and the striker's opponent, boxing gloves were implemented within the sport of boxing (1,3,(5)(6)(7)(8)12,13). Diesselhorst et al found that wearing hand protection when striking greatly reduces the risk of hand injury (3).…”
Section: Introductionmentioning
confidence: 99%
“…In order to compare the impact of the training period on energy expenditure, a one-way analysis of variance with repeated measures was applied. Experiments show that boxing training consumes a lot of energy, and different boxing moves consume different energy, but his research lacks a detailed study of boxing effects [1]. Kasiri et al propose a robust framework for automatic classification of boxers' punches.…”
Section: Introductionmentioning
confidence: 99%